Harnessing the Potential of Storytelling on Social Media: A Game-Changer for Halal Tourism Marketing Strategies - Setiawan, Harry Setiawan; Afifah, Nur; Mustaruddin, Mustaruddin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study aims to investigate the role of storytelling on social media as a moderating variable in the relationship between Muslim tourists' emotional experiences and their intention to revisit halal tourism destinations. With the growing Muslim population and increasing purchasing power, the halal tourism industry has significant growth potential. However, to capitalize on this potential, a better understanding of the factors influencing Muslim tourists' experiences and behavior is needed. Using a quantitative approach and structural equation modeling, this research examines the impact of storytelling on social media on the relationships between halal destination attributes, halal-friendly services, emotional experiences, and revisit intentions. The analysis results demonstrate that storytelling on social media significantly moderates the relationship between emotional experiences and revisit intentions, strengthening the influence of emotional experiences on post-visit behavioral intentions. These findings contribute to the advancement of tourism marketing and consumer behavior theories, as well as provide practical implications for the halal tourism industry in designing effective marketing strategies through social media storytelling.